INCREASING TRENDS OF CENTRAL PRECOCIOUS PUBERTY AMONG CHILDREN IN HOSPITAL PUTRAJAYA, 2004 TO 2024: A DESCRIPTIVE STUDY - AX, Jayne Ong; Hong, Janet Y H; Selveindran, Nalini M. (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Temporal trends worldwide demonstrate evidence of an earlier onset and progression of puberty worldwide. This study aims to describe the trends in Precocious Puberty among children in Hospital Putrajaya between 2004 to 2024. Data retrieved from the electronic database were reviewed. All patients diagnosed to have precocious puberty (i.e., onset of puberty before age 8 years for girls and 9 years for boys) in the Department of Paediatric Endocrinology of Hospital Putrajaya from January 2004 until April 2024 were included (n = 89). These patients were stratified according to the diagnosis; children diagnosed with Idiopathic Central Precocious Puberty (CPP) and normal variant puberty (i.e., Premature thelarche (PT) or Premature Adrenarche (PA). CASE Overall, a total of 89 children (86 (96.6%) girls; median [interquartile] age at diagnosis for boys, 7 [6;10] years; for girls, 7 [2;9] years) were registered with a diagnosis of CPP, PT, PA. Majority were Malay, 54 (60.7%), 25 (28.1%) were Chinese, 8 (9%) were Indian and 2 (2.2%) were Nigerians. Majority of the cases were idiopathic CPP, 81 (91%); with a median [interquartile] LH:FSH ratio of 1.4 [0.16;7.23]. The MRI findings show normal findings in 30 (35.3%), pituitary microadenoma in 29 (34.1%), and pineal gland cysts in 1 (1.12%). There was a general increase in the number of cases of CPP over time; between 2013 to 2018; 23 (25.8%), and a greater rise between 2019 to 2024; 61 (68.5%). Nearly half of the cohort had a body mass index (BMI) of overweight or obese 40 (41.3%); with median [interquartile] bone age, 4 [2;7]. CONCLUSION This study demonstrated an increase in the number of patients with central precocious puberty over 20 years. We also demonstrated a possible association with an increased BMI and earlier onset of puberty in girls.